Human Resource Management for Public-Private Partnerships: Lessons from Project Driven Organization for Malaysia’s Public Service Sector - Mohd Ikmal Hisyam; Bakar, Ahmad Naqiyuddin; Noor, Nurul Hidayana Mohd (Journal of Human Capital Development (JHCD), 2025)
Given that Public-Private Partnership (PPP) as a project requires specialized competencies in project management (PM), an evident gap exists between these requirements and the generalized support provided by current centralized Human Resource Management (HRM) in the public service sector in Malaysia. Evidence suggests that the current HRM framework might inadequately support competency development for these dynamic and complex projects, limiting managerial effectiveness. Following the PRISMA 2020 protocol, this systematic literature review includes empirical studies from Scopus and Web of Science published between 2000 and 2024 in analyzing HRM requirements for project-driven organizations. Using automation and qualitative methods, 25 documents were selected, identifying nine themes contextualizing HRM practices and underscoring the need for competency-specific HRM that aligns with a PM requirement. The review offers comprehensive insight into HRM, public administration, and PM literature. It advocates for tailored HRM policy and practices emphasizing competency development specific to project requirements, such as PPP in public service sector administration, and providing better insight for policymakers seeking to enhance public service sector efficiency and strengthen PPP implementation in Malaysia.